Pelatihan Pembuatan Temulawak Serbuk Instan di Daerah Lubuk Minturun Kecamatan Koto Tangah Kota Padang - Futeri, Renny; Syafrinal, Syafrinal; Riani, Pevi; Armin, Muhammad Ikhlas; Dewati Samah, Selfa; Putri, Melysa; Anwar, Hazil (Journal of Industrial Community Empowerment, 2022)
Curcuma can be used to maintain and improve body health as well as treat disease. Instant powdered curcuma drink is one of the curcuma plant's processed products.People in the Lubuk Minturun Koto Tangah District, Padang City have natural and human resources that can be utilized through training programs for creating instant powdered curcuma. This exercise drew a total of 25 women, including housewives and teenagers. There are three steps to this community service activity: lectures, demonstrations, and practice. Because the production method is simple and the tools and materials required are readily available, more than 90% of the participants in this activity were able to comprehend the process of making instant powdered curcuma. It is intended that by participating in this activity, the community would be able to increase entrepreneurial prospects and so boost the economy.